Biotechnological approaches in propagation and evaluation of Miscanthus giganteus - Петюх, Г. П.; Пришляк, Р. І. (Problems of Environmental Biotechnology, 2018)
The paper describe brief review of plant multiplication approaches of bioenergy crop miscanthus, including using of biotechnology methods, as well as main directions of researches to carry out comparative analysis for different plant materials of Miscanthus x giganteus by molecular genetic methods.